Microelectronic flowmeter on the basis of transistor structure with an active inductive element - Osadchuk, V. S.; Osadchuk, O. V.; Yushchenko, Yu. A. (Visnyk of Vinnytsia Politechnical Institute, 2010)
In article the opportunity of transformation of the charge of the gas environment is shown on the basis of the autogenerating device which will consist of three bipolar transistors, and also electric bridge in which shoulders sensitive elements are included on the basis of semiconductor diodes. Analytical dependences of function of transformation and the equation of sensitivity are received. Theoretical and experimental research have shown, that sensitivity of the developed flowmeter a frequency output makes 32…56 kHz/ Liter in one hour.